2019
DOI: 10.1002/macp.201900223
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Acyclic Diene Metathesis Polycondensation

Abstract: Bulk acyclic diene metathesis (ADMET) polymerization performed in the melt at temperatures up to 175 °C is completed using a cyclic (alkyl)(amino) carbene (CAAC) ruthenium‐based Grubbs catalyst. High temperature stability is investigated at temperatures well above conventional ADMET chemistry, leading to the highest weight‐average molecular weights ever achieved for any ADMET polymer. A study of isomerization tendency (double bond migration) is done via self‐metathesis of a small molecule model compound using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…As expected, and as highlighted by Wagener and co-workers, the propensity of (CAAC)ruthenium catalysts to completely inhibit isomerization processes remains contingent on the nature of the olefin. This was demonstrated in the homodimerization of the anthracene-substituted olefin 6 in the presence of Ru-3 at 100 °C, which afforded up to 29% of the isomerization product 7 (Scheme ).…”
Section: (Caac)ruthenium Catalysts In Olefin Metathesismentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, and as highlighted by Wagener and co-workers, the propensity of (CAAC)ruthenium catalysts to completely inhibit isomerization processes remains contingent on the nature of the olefin. This was demonstrated in the homodimerization of the anthracene-substituted olefin 6 in the presence of Ru-3 at 100 °C, which afforded up to 29% of the isomerization product 7 (Scheme ).…”
Section: (Caac)ruthenium Catalysts In Olefin Metathesismentioning
confidence: 99%
“…Capitalizing on these results, Wagener and co-workers extended the study to the bulk polymerization of 1,9-decadiene 67 and bis­(pent-4-en-1-yl)­sulfone 69 (Scheme ). While excellent polycondensation results were obtained in both cases, the authors demonstrated the stability of (CAAC)ruthenium catalyst Ru-3 up to 175 °C, with a slight loss of reactivity at 200 °C. While this latter result is presumably due to slow catalyst degradation, it clearly shows that CAAC complexes can retain their activities despite the very high working temperatures necessary to maintain a liquid state in high-crystallinity polymers.…”
Section: (Caac)ruthenium Catalysts In Olefin Metathesismentioning
confidence: 99%
“…Grubbs-type catalysts have wide applications 11 in ringopening metathesis polymerization (ROMP), [12][13][14] acyclic diene metathesis (ADMET) polymerization, [15][16][17] metathesis cyclopolymerization (MCP), [18][19][20][21][22][23] and the above-mentioned MDP of unsaturated polymers for the preparation of structure-controllable polymers, due to their high catalytic activity, good stabi-lity in air, and functional group tolerance. However, there are no scientific works available on the combined MDP of unsaturated polymers with the metathesis polymerization of monomers for providing block copolymers, except for a few examples related to combining MDP of NR gloves with ROMP of a cycloolefin containing an oligo-1,4-cis-isoprene side chain 1 or combining the CM depolymerization of PBD with ROMP of a cycloolefin in the presence of CTA, affording low viscosity liquid of telechelic copolydienes.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to mention that polymerizations were performed in solution instead of bulk in order to overcome limitations due to high viscosity in reaching high molar mass. [ 26 ] Polarclean (ethyl‐5‐(dimethylamido) ‐2‐methyl‐5‐oxopentanoate) was the choice of solvent as it is recognized as an eco‐friendly solvent, featuring a high boiling point and a lower toxicity than toluene, o ‐chlorobenzene or N, N ‐dimethylformamide. After reacting monomer M1 with HG‐II catalyst (2.0 mol%/molecule), under dynamic vacuum (1.0–0.1 mbar) at a temperature range from 65 to 75 °C in Polarclean (0.6 m ) for 3 h, the targeted polymer P1 was isolated with an M n of 20 400 g mol −1 ( Ð of 1.9, as determined by size exclusion chromatography (SEC) relative to polystyrene standards in tetrahydrofuran (THF) as eluent, black line in Figure 1D).…”
Section: Introductionmentioning
confidence: 99%